HUBUNGAN BUDAYA DISIPLIN TERHADAP HASIL BELAJAR PESERTA DIDIK MATA PELAJARAN IPS KELAS VII SEMESTER GENAP DI SMP NEGERI 3 SITUBONDO TAHUN PELAJARAN 2017/2018 - Lusi Endang Sri damayanti; Achmad Zainuri (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2018)
The low learning achievement of students is known from the relatively low semester semester of Social Semester subjects. In social studies subjects the teacher establishes minimum completeness criteria (KKM) of 75. The research design uses expost facto. Data collection techniques in the form of observation, interviews, documentation and questionnaires. After data analysis and hypothesis testing, the correlation coefficient level between learning outcomes (Y) and time discipline culture (X1) is obtained by ignoring the disciplinary culture of action (X2) and the discipline discipline discipline (X3) of 0.4561. While the correlation coefficient level between learning outcomes (Y) and the discipline of deed culture (X2) ignores the time discipline culture (X1) and the discipline discipline discipline (X3) is 0.4052, while the correlation coefficient level between learning outcomes (Y) with a culture of disciplinary discipline (X3) by ignoring the time discipline culture (X1) and the discipline of deed culture (X2) of 0.1257. and the level of correlation coefficient between the three independent variables simultaneously with the criteria Ry (1,2,3) of 0.663. In a significant influence between disciplinary culture on learning outcomes of social studies students in class VII even semester in Situbondo 3 Public Middle School Academic Year 2017/2018. There is a significant influence between the culture of time discipline on the learning outcomes of social studies students of class VII even semester in Situbondo 3 Public Middle School Academic Year 2017/2018. There is a significant influence between the disciplinary culture of action on the learning outcomes of social studies students of class VII even semester in Situbondo 3 Public Middle School Academic Year 2017/2018. There is no significant effect between the culture of disciplinary discipline on the learning outcomes of social studies students of class VII even semester in Situbondo 3 Public Middle School Academic Year 2017/2018.